Men of justice and ordinances: mestizos’ participation in the colonial administration of Rio Grande Captaincy (XVIII and XIX centuries) - Araújo, Maiara Silva; Macedo, Helder Alexandre Medeiros de (Em Perspectiva, 2020)
This article aims at examine the mestizo subject profile between eighteenth and ninetennth century through the case study of Orphan Judge Manuel de Souza Fortes. The mestizo subject occupied administrative, judicial and military crafts at Capitania do Rio Grande and this study aims to analyse who were these mestizos, which instruments used to be used for them to insert yourselves in colonial administration. This text analyse judicial and parochial documents and dialogues with authors like Gouvêa, Fragoso and Macedo. It presuppose a negotiated relationship between colony and metropolis and because this the colonial institutions worked not only for Crown but also for internal affairs. An exemple was the mestizo insert in colonial bureaucracy in spite of miscegenation used to be a obstacle for access administrative crafts according Old Regime. So this article purpose to understand who were the mestizos and how they accessed the colonial bureaucracy in backlands.